Correlation between in vitro and in vivo activity of antimicrobial agents against gram-negative bacilli in a murine infection model. - Fantin, B (1991)
We studied the relationship between in vitro susceptibility tests (MICs, MBCs) and in vivo activity of tobramycin, pefloxacin, ceftazidime, and imipenem against 15 gram-negative bacilli from five different species in a murine thigh infection model. Complete dose-response curves were determined for each antimicrobial agent against each strain, and three parameters of in vivo activity were defined: maximal attainable antimicrobial effect (i.e., reduction in log10 CFU per thigh compared with untreated controls) at 24 h (Emax), total dose required to reach 50% of maximal effect (P50), and total dose required to achieve a bacteriostatic effect (static dose). Pefloxacin demonstrated the greatest Emax (P less than 0.05). Tobramycin was the most potent antimicrobial agent, as indicated by its having the lowest static dose/MIC ratio (P less than 0.002). Log10 P50s and static doses correlated significantly with log10 MICs or MBCs for the 15 strains of each antibiotic (P less than 0.01) except imipenem (P greater than 0.50). The greater potency of imipenem against the three Pseudomonas aeruginosa strains than against strains of the family Enterobacteriaceae (P less than 0.01) explained this lack of correlation. A longer duration of postantibiotic effect for imipenem against P. aeruginosa (P = 0.02) contributed to its increased potency against these strains. We conclude that in vitro susceptibility tests correlated well with in vivo activity in this animal model and that variations in potency among the four antimicrobial agents could be explained by differences in pharmacokinetics or pharmacodynamic activity.